2023
DOI: 10.1002/jcb.30480
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of liquid–liquid phase separation propensities of HSV‐1 proteins and their interaction with host factors

Sushma Subedi,
Niharika Nag,
Harish Shukla
et al.

Abstract: In recent years, it has been shown that the liquid–liquid phase separation (LLPS) of virus proteins plays a crucial role in their life cycle. It promotes the formation of viral replication organelles, concentrating viral components for efficient replication and facilitates the assembly of viral particles. LLPS has emerged as a crucial process in the replication and assembly of herpes simplex virus‐1 (HSV‐1). Recent studies have identified several HSV‐1 proteins involved in LLPS, including the myristylated tegu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 121 publications
0
1
0
Order By: Relevance
“…Certain compartments exhibit liquid properties and are formed through a process known as liquid–liquid phase separation (LLPS), analogous to the formation of oil droplets in water [ 45 ]. There is a hypothesis suggesting that the nuclear VRCs of DNA viruses, such as HSV-1, are also phase-separated condensates [ 46 , 47 ]. Seyffert et al demonstrated that the HSV-1 transcription factor ICP4 has the ability to induce protein condensation, thereby imparting liquid-like properties to the VRC [ 48 ].…”
Section: The Replication Process Of the Virus Within The Cellmentioning
confidence: 99%
“…Certain compartments exhibit liquid properties and are formed through a process known as liquid–liquid phase separation (LLPS), analogous to the formation of oil droplets in water [ 45 ]. There is a hypothesis suggesting that the nuclear VRCs of DNA viruses, such as HSV-1, are also phase-separated condensates [ 46 , 47 ]. Seyffert et al demonstrated that the HSV-1 transcription factor ICP4 has the ability to induce protein condensation, thereby imparting liquid-like properties to the VRC [ 48 ].…”
Section: The Replication Process Of the Virus Within The Cellmentioning
confidence: 99%